Introduction of a new classification for resin composites with enhanced color adjustment potential - KORKUT, BORA; TARÇIN, BİLGE; YILMAZ ATALI, PINAR (My University, 2023)
Purpose of Review With the introduction of new resin-based composites (RBC) based on their adjusted shade properties, there is a need for an additional classifcation for such materials. This review discusses and suggests a new classifcation for the RBCs. Recent Findings The classifcation of RBCs depends on diferent compositions and characteristics such as inorganic fller type, shape and size, resin matrix, polymerization modes, level of viscosity, clinical application protocol, and indications. The classifcation is generally focused on the fller size, fller type, and composition. Recently, some manufacturers have created contemporary esthetic RBC kits with enhanced color adjustment potentials. This ability is considered very specifc and particularly depends on the shade and the brand of the selected composite kit. The current RBC classifcations are generally inadequate in describing the shade-matching abilities of these new materials. Summary An additional universal terminology and related classifcation are required, describing the level of color adjustment potential of contemporary RBCs. The suggested new classifcation divides RBCs as ‘polyshade,’ ‘simplyshade,’ and ‘monoshade universal.’
Keywords: Monoshade universal; Simplyshade; Polyshade; Resin composite; Color adjustment